The Influence of Food Quality, Store Atmosphere on Consumer Satisfaction at Pecel Lele Wonosobo Sudirman Pekanbaru - Mandataris; Thalita Salsabilla Puteri (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of food quality, store atmosphere on consumer satisfaction at Pecel Lele Wonosobo Sudirman Pekanbaru. The method used in this study is quantitative statistical method. The sample in this study amounted to 100 respondents who were determined using purposive sampling and using questionnaires as data collection instruments. From data analysis which includes validity tests, reliability tests, linear regression analysis, hypothesis tests and determination coefficient tests, it was found that food quality has a significant effect on consumer satisfaction, store atmosphere has a significant effect on consumer satisfaction and the results of F food quality and store atmosphere tests simultaneously have a significant effect on consumer satisfaction at Pecel Lele Wonosobo Sudirman Pekanbaru.